A Note on using Graphs in Regular Scheduling Problems - Peter Czimmermann (Communications - Scientific letters of the University of Zilina, 2003)
This paper deals with regular permutation scheduling on graphs. Peško and Czimmermann introduced this problem (in [3]) and it is generalisation of a matrix permutation problem. The goal is to minimise differences between row sums of a real matrix that represents a schedule, but external conditions don’t allow moving matrix elements arbitrarily. The conditions can be represented by permutation obtained from a certain graph.